Impact of climate change on agriculture in Irrigation District 005, Chihuahua, Mexico - Lucero López, Claudia Yessenia; Castruita Esparza, Luis Ubaldo; Legarreta González, Martin Alfredo; Olivas García, Jesús Miguel; Uranga Valencia, Luisa Patricia; Luján Álvarez, Concepción (Revista Mexicana de Ciencias Agrícolas, 2022)
It is expected that the sector most economically affected by climate change is agriculture, being affected by the decrease in economic income. The objective of the research was to know the impact of the climate change in the agriculture in Irrigation District 005 located in the state of Chihuahua. This, through the application of surveys in the year 2020. Chi-square tests were performed, obtaining that, of the respondents: 40% [X2 (1,38.32) p <.001] owns more than 20 hectares; 65% cultivate mainly pecan walnut (Carya illinoinensis); 97.89% [X2 (1,87.17) p <.001)] have heard about of climate change and 44.09% [X2 (1,55.33) p <.001)] define it as pronounced climatic variation between seasons. The multiple correspondence analysis estimated that the variables that presented greater inertia for the first dimension were: zero tillage (M1), change of crop type (M3), water harvesting techniques (M4), others (M5) and percentage of contribution (Cmedidas); For the second dimension, those that presented greater inertia were: has had economic losses (Peconomicas), period most affected (Periodo), cause of the affectation (Causa), percentage of economic losses (Pp). Two multinomial logistic regression models were run, the measures applied to reduce the effects of climate change were zero tillage and the use of organic products. The results obtained showed that with the increased age of the producers, the possibility that they are know the climate change, its causes, and choose to take out insurance decreases. Finally, that it is necessary to apply more than one mitigation / adaptation measure to counteract climate change.